Multi-Agent-Based Macroeconomic Modelling - Karajz, Sándor (Theory, Methodology, Practice – Review of Business and Management, 2019)
Macroeconomic modelling emerged at the end of the 20th century and by the first decade of the 21st century it had been widely accepted. However, the financial crisis of 2007 followed by the real economy crisis exposed the weaknesses of dynamic stochastic general equilibrium models (DSGE) and agent-based models became favoured. Agent-based models – better reflecting reality– assume that individuals are capable of learning from past experiences. In economics, aggregation is considered to be fundamental in the analysis of macroeconomic processes, leading to question such as: How can processes describing macroeconomics and related indicators be obtained from results generated from decisions made at a microeconomic level? Is the applied method appropriate? Are synergy possibilities considered? This study attempts to provide answers to these questions.